Quality of Work Life of Mental Health Professionals in Albania - Xhakollari, Lediana (Richtmann Publishing, 2013)
Numerous studies conducted on the quality of working life have shown that a high quality of work life leads to a higherproductivity of the organization, and higher performance, motivation, commitment, pride, satisfaction of employees at work.The subjects of this study are mental health workers in Albania. This article reviews the meaning of quality of work life andanalyses constructs of quality of work life based on Walton model. The constructs of quality of work life discussed are,adequate and fair compensation, safe and healthy working conditions, opportunity to use and develop human capacities, futureopportunity for continued growth and security, social integration in the work organization, constitutionalism in the workorganization, work and total life space, the social relevance of work life. This is mainly a quantitative study, with some elementsof qualitative methods. Specifically, are used the scale measuring satisfaction with the quality of working life (adapted from themodel of Walton), interviews and observations. At the conclusion of the study came out that overall mental health workersgeneral are satisfied with their quality of work life. Quality of work life is positively related to all its constructs.